Expression of growth hormone-releasing hormone receptors in apocrine adnexal tumours and apocrine glands of the skin - Kővári, Bence; Kocsis, Lajos; Varga, Erika; Cserni, Gábor (Polish Journal of Pathology, 2018)
Encouraged by our previous finding of growth hormone-releasing hormone receptor (GHRH-R) expression in metaplastic and neoplastic apocrine breast epithelium, we examined a small series of skin adnexal tumours with various degrees of apocrine (oxyphilic) differentiation, as well as normal axillary and anogenital apocrine sweat glands, for the expression of GHRH-R. Sections of formalin-fixed paraffin-embedded tissue blocks were immunostained for gross cystic disease fluid protein-15 (GCDFP-15) and androgen receptor (AR), to prove apocrine differentiation and correlate it with areas of GHRH-R expression. All but one of 19 tumours with apocrine epithelium and all five benign apocrine glands stained with both anti-GHRH-R antibodies used, each labelling a different domain of the receptor. Non-apocrine areas of the tumours and four eccrine tumours without oxyphilic features did not stain, but most sebaceous glands and some eccrine glands were labelled. Our data suggest that anti-GHRH-R antibodies highlight apocrine differentiation at extramammary sites also. Although GHRH-R seems to have a sensitivity comparable to classic apocrine markers such as AR and GCDFP-15, it seems to be inferior in specificity. The GHRH-R labelling of apocrine glands and neoplastic epithelium might also interfere with the emerging anti-GHRH targeted treatment of some malignancies acting on these receptors.